Fuzzy logic use case within the built environment for optimizing sustainability versus cost in the material selection process - Smith, Kyle Abbott; Mostafiz, Rubayet Bin; Friedland, Carol; Nahmens, Isabelina (Frontiers in Built Environment, 2025)
This study aims to investigate the application of fuzzy logic in decision-making within the Built Environment. The research focuses on achieving a balance between reducing carbon emissions and increasing costs in the selection of materials and equipment. This balance is measured by Life Cycle Carbon Emissions (LCCE) and is evaluated using a Life Cycle Assessment (LCA) methodology. By modeling fuzzy logic against classical binary logic within MATLAB, the study demonstrates how fuzzy logic’s “degrees of truth” may be utilized to construct customized stakeholder buy-in profiles and also achieve increased mathematical precision. These decision-maker stakeholder profiles reflect different interpretations of linguistic expressions of value in terms of cost against carbon reduction trade-offs. The research develops a three-dimensional control surface by using the Fuzzy Logic Toolbox in MATLAB. This surface serves as a visual tool for purchasing professionals to optimize these trade-offs on a scale, which provides a practical strategy for large-scale construction projects.